2021
DOI: 10.1212/wnl.0000000000012341
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Network Changes and Conversion to Cognitive Impairment in Multiple Sclerosis

Abstract: OBJECTIVE:To characterize functional network changes related to conversion to cognitive impairment in a large sample of MS patients over a period of 5 years.METHODS:227 MS patients and 59 healthy controls (HCs) of the Amsterdam MS cohort underwent neuropsychological testing and resting-state fMRI at two time points (time-interval 4.9±0.9 years). At both baseline and follow-up, patients were categorized as cognitively preserved (CP, N=123), mildly impaired (MCI, Z<-1.5 on ≥2 cognitive tests, N=32) or impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 38 publications
(67 reference statements)
2
38
0
Order By: Relevance
“…This study involves a retrospective analysis of prospectively attained longitudinal data from the Amsterdam multiple sclerosis cohort, 23 , 24 including a total of 332 multiple sclerosis patients and 96 healthy controls (HCs) with available functional MRI data who were recruited between 2008 and 2012. 12–14 , 24–29 Functional network dynamics in these participants was described previously.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This study involves a retrospective analysis of prospectively attained longitudinal data from the Amsterdam multiple sclerosis cohort, 23 , 24 including a total of 332 multiple sclerosis patients and 96 healthy controls (HCs) with available functional MRI data who were recruited between 2008 and 2012. 12–14 , 24–29 Functional network dynamics in these participants was described previously.…”
Section: Methodsmentioning
confidence: 99%
“…This study involves a retrospective analysis of prospectively attained longitudinal data from the Amsterdam multiple sclerosis cohort, 23 , 24 including a total of 332 multiple sclerosis patients and 96 healthy controls (HCs) with available functional MRI data who were recruited between 2008 and 2012. 12–14 , 24–29 Functional network dynamics in these participants was described previously. 14 In total, 234 multiple sclerosis patients and 60 HCs returned for a 5-year follow-up between 2014 and 2017, of whom rs-fMRI and neuropsychological assessment was available at both time points for 230 patients (48 ± 11 years; 83 male) and 59 HCs (46 ± 10 years; 28 male).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Decreased anticorrelation between DMN and attention networks was related to worse behavioral performance in HC 55 , moreover increased functional connectivity between VAN and DMN was observed in pwMS who had cognitive impairment compared to those without cognitive impairment and HC. 56 Even though we did not have cognitive scores for our cohort, previous studies have identified a strong association between disability and cognitive impairment in MS. 57 Our results suggest that dysfunction of the interaction between the VAN and DMN states may result in greater energetic demand between these states in pwMS with evidence of disability compared to the other groups. Finally, our results also showed greater transition energy between SOM+ and VIS-was associated with pwMS who had disability.…”
Section: Discussionmentioning
confidence: 96%